Lyric address in Dutch literature, 1250-1800 - Haven, Cornelis van der 1978-; Pieters, Jürgen 1969- (Amsterdam University Press, 2020)
Lyric Address in Dutch Literature, 1250-1800 provides accessible and comprehensive readings of ten Dutch lyrical poems, discussing each poem's historical context, revealing its political or ideological framing, religious elements, or the self-representational interests of the poet. The book focuses on how the use of the speaker's "I" creates distance or proximity to the social context of the time. Close, detailed analysis of rhetorical techniques, such as the use of the apostrophe, illuminates the ways in which poetry reveals tensions in society
Title from publisher's bibliographic system (viewed on 14 Dec 2020)
Cover; Table of Contents; Lyric Address: By Way of an Introduction; Cornelis van der Haven and Jürgen Pieters; 1. Staying in Tune with Love; Hadewijch, 'Song 31' (thirteenth century); Anikó Daróczi; 2. O Brittle Infirm Creature; Anonymous (Gruuthuse MS), 'Song' (c. 1400); Clara Strijbosch; 3. Lyric Address in Sixteenth-Century Song; Aegied Maes (?), 'Come hear my sad complaint' (before 1544); Dieuwke van der Poel; 4. An Early Modern Address to the Author; Pieter Corneliszoon Hooft, 'My love, my love, my love' (1610); Britt Grootes; 5. Parrhesia and Apostrophe
Elizabeth Wolff-Bekker, 'To Miss Agatha Deken' (1777)Maaike Meijer; 10. Nature, Poetry and the Address of Friends; Jacobus Bellamy, 'To my Friends' (1785); Cornelis van der Haven; Epilogue; Lyrical and Theatrical Apostrophe, from Performing Actor to Textual Self; Frans-Willem Korsten; List of Poems (Sources); Index of Names
Joost van den Vondel, 'Salutation to the Most Illustrious and Noble Prince Frederick Henry' (1626)Marrigje Paijmans; 6. Lyrical Correspondence; Maria Tesselschade Roemers Visscher, 'To My Lord Hooft on the death of Lady Van Zuilichem' (1637); Marijn van Dijk; 7. The Apostrophic Interpellation of a Son; Jan Six van Chandelier, 'My Father's corpse addressing me' (1657); Jürgen Pieters; 8. Guilty Pleasure; Hubert Korneliszoon Poot, 'Thwarted attempt of the Poet' (1716); Christophe Madelein; 9. Same-Sex Intimacy in Eighteenth-Century Occasional Poetry
Keywords: Geschichte 1250-1800; Dutch poetry / History and criticism; Dutch literature / History and criticism; Niederländisch; Rhetorik; Adressat; Erzählsituation; Zeithintergrund; Lyrik; Aufsatzsammlung